DAMPAK PERAN PEREMPUAN DALAM PEMBANGUNAN MASYARAKAT PEDESAAN TRANSMIGRASIDAMPAK PERAN PEREMPUAN DALAM PEMBANGUNAN MASYARAKAT PEDESAAN TRANSMIGRASI - Ashari Ismail (Universitas Negeri Makassar, 2023)
ABSTRACTThe role of women in development is a role that is demanded, including in transmigration rural development. The role of women is not only in the domestic sphere, but also in the public role. This basic research was conducted in the Baras Sembilan transmigration area, Pasangkayu, to explore the impact of women's developmental roles. The research method used is a qualitative method, with a qualitative descriptive approach. The results of the research show that the role of transmigrant women has an impact on: women's autonomy in decision making, the birth of family equality, and broad employment opportunities. Keywords: The Impact of the Role of Transmigrant Women